Description of the final stadium larva of Bayadera serrata Davies & Yang, 1996 (Odonata: Euphaeidae) from Thailand - Keetapithchayakul, Tosaphol Saetung; Sripanya, Jutamas; Phlai-Ngam, Sirikamon; Tungpairojwong, Nisarat (Zootaxa, 2020)
The damselfly genus Bayadera Selys, 1853 comprises 17 species, but the larvae of only four species have been described. Here we describe the final stadium larva of another species—Bayadera serrata Davies & Yang, 1996. Larvae were collected from a headwater stream at Nam Nao National Park, Phetchabun Province, Thailand. The larva of B. serrata is distinguished from congener species following the presence of one to three distinct spines on the genae, two pairs of setae on the ligula, one pair of setae on the ventral side of prementum, the presence of three teeth of the distal end of the labial palp, the presence of a plate-like spine on the gonapophyses, the presence of a row of rod-like setae on the distal end of the tibial comb, the presence of a cluster of long simple setae on the abdominal terga S3–9, and the presence of short terminal filament of the caudal gills. The larvae of genus Bayadera have been compared with other known larvae from family Euphaidae. Key is provided to the genera with known Southeast Asian euphaeid larvae: Anisopleura, Bayadera, and Euphaea.